The Validity and Reliability Characteristics of the M-BACK Questionnaire to Assess the Barriers, Attitudes, Confidence, and Knowledge of Mental Health Staff Regarding Metabolic Health of Mental Health Service Users - Watkins, Andrew; Rosenbaum, Simon; Ward, Philip B.; Patching, Joanna; Denney-Wilson, Elizabeth; Stein-Parbury, Jane (Frontiers in Public Health, 2017)
Abstract Background: Addressing the burden of poor physical health and the subsequent gap in life expectancy experienced by people with mental illness is a major priority in mental health services. To equip mental health staff with the competence to deliver evidence-based interventions, targeted staff training regarding metabolic health is required. In order to evaluate the effectiveness of staff training regarding metabolic health, we aimed to develop a succinct measure to determine the barriers, attitudes, confidence and knowledge of health practitioners through the development and test-retest reliability of the Metabolic-Barriers, Attitudes, Confidence and Knowledge Questionnaire (M-BACK). Methods: The M-BACK questionnaire was developed to evaluate the impact of specialised training in metabolic health care for mental health nurses. Content of the M-BACK was developed from a literature review and refined by an expert review panel and validated via a piloting process. To determine the test-retest reliability of the M-BACK, 31 nursing students recruited from the University of Notre Dame, Sydney completed the questionnaire on two separate occasions, seven-days apart. Intra-class correlation coefficients (ICC) were calculated for the total score, as well as each of the four domains. Results: Pilot testing was undertaken with a sample of 106 mental health nurses with a mean age 48.2, ranging from 24 years to 63 years of age, who participated in six training courses. Questionnaire development resulted in a 16-item instrument, with each item is scored on a five-point Likert scale ranging from ‘strongly disagree’ to ‘strongly agree’. Test-retest reliability of the M-BACK was completed by 30 of 31 nursing students recruited, ICCs ranged from 0.62 to 0.96. Conclusion: The M-BACK is a reliable measure of the key elements of practitioner perceptions of barriers, and their knowledge, attitudes and confidence regarding metabolic monitoring in people with mental illness. It can be used to assess the effectiveness of interventions aimed at increasing uptake of metabolic monitoring, a key component of programs to reduce the life expectancy gap in people living with severe mental illness. Keywords: Severe mental illness, Physical health, Education, Training, Evaluation tool, Service delivery, Health outcomes, Metabolic Syndrome